Species Counterpoint: Pendekatan Dalam Pembelajaran Kontrapung - Nainggolan, Oriana Tio Parahita (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Abstract: As a part of music theory, Counterpoint dealing with a combination of melody in contrary motion. It is focused on combining melody between cantus firmus and counterpoint. In learning counterpoint, there are two approaches which usually used, free Counterpoint and strict counterpoint (it is well known as species counterpoint). The free counterpoint method allows writing counterpoint melody without paying attention to Counterpoint rules. While in strict counterpoint does not give freedom to write counterpoint melody, hence in must follow Counterpoint rules. Based on an early observation of this study, it found that the free counterpoint method did not give a strong understanding of basic counterpoint to the students. It is showed that students are confused when they made a Counterpoint melody. They stated that they were confused about how to start the melodies and also how to develop their melody because they donâ€™t have a strong basis of counterpoint rules. This research aims to analyze the role of species counterpoint in giving a rudiment to the students. Species counterpoint used here as a pedagogical tool, which makes students learned through several steps called species. This is qualitative research. The data acquired from observation and interviews during learning Counterpoint at Music Education Study Program, Faculty of Performing Arts, Institut Seni Indonesia Yogyakarta. The results showed that species counterpoint builds a strong fundamental theory in writing counterpoint melody. Moreover, it also helps students to increase their skills in writing a counterpoint melody.Keywords: Counterpoint, Cantus Firmus, Species Counterpoint, Melody.Â Abstrak: Kontrapung merupakan cabang dari Teori Musik untuk menyusun kombinasi melodi secara berlawanan antara cantus firmus dan counterpoint. Dalam pembelajaran Kontrapung terdapat dua pendekatan yaitu free counterpoint dan strict counterpoint (species counterpoint). Free counterpoint memberikan kebebasan dalam membuat melodi Kontrapung, sementara strict counterpoint harus mempertimbangkan berbagai macam kaidah dalam membuat melodi Kontrapung. Berdasarkan observasi awal, penggunaan free counterpoint dalam pembelajaran Kontrapung tidak memberikan dasar yang kuat untuk dapat membuat melodi Kontrapung. Untuk mengatasi hal tersebut, maka sebaiknya pembelajaran Kontrapung dilakukan dengan menggunakan pendekatan species counterpoint. Penelitian ini bertujuan untuk mendeskripsikan penggunaan species counterpoint pada pembelajaran Kontrapung dalam membuat melodi Kontrapung. Penelitian ini merupakan penelitian kualitatif deskriptif. Data penelitian didapat dari hasil observasi dan wawancara yang dilakukan selama pembelajaran Kontrapung di Program Studi S-1 Pendidikan Musik, Fakultas Seni Pertunjukan, Institut Seni Indonesia Yogyakarta. Hasil penelitian menunjukkan bahwa pembelajaran Kontrapung dengan menggunakan pendekatan species counterpoint dapat meningkatkan pemahaman terhadap kaidah-kaidah Kontrapung dalam membuat melodi Kontrapung, selain itu pembelajaran Kontrapung dengan species counterpoint juga meningkatkan keterampilan dalam membuat melodi Kontrapung.Kata Kunci: Kontrapung, Cantus Firmus, Species Counterpoint, Melodi.Â